Desafios e possibilidades do ensino da língua inglesa para surdos - Carvalho, Raquel Araújo Mendes de (2014)
The present study aims to observe and describe the system of cultural meanings of the English Language teaching and learning process, as well as its challenges and possibilities for deaf students. This qualitative research is an ethnographic based study, which studies a second year high school students inserted in a Youth and Adult Education (YAE). This group of students studies in a public school that has a special education for deaf people and it is also an inclusive school. At first, this school worked only as a special school for deaf students. Nowadays, due to the policy of inclusion, besides deaf students, this school also admits students who are listeners. The participants of this research were compound by eleven students (6 deaf students and 5 listeners), the English Teacher of this group and the Brazilian Sign Language Interpreter, who is also the participant-researcher of this study. This study lasted a whole school semester and the observations were made through audiovisual recordings of classes and interviews, field notes, and gathered documents. Regarding the presented cultural context, there was an attempt to understand the teaching practices of the English Language teaching for deaf students, the English Teacher’s conceptions of Foreign Language teaching, the cultural aspects of each language used in this process (Brazilian Sign Language, English and Portuguese), the influence of the inclusive process in that context and the interaction between the individuals studied. In the analysis, it was used the concept of cultural domains from ethnography (SPRADLEY, 1980). Conceptions about Deaf People Education and public policy of inclusion were discussed in the analysis. The analyzed data show that the researched school makes an effort to adapt itself according to the reality presented by the inclusive education. Another important fact observed during the English classes is that there is a lack of interaction between deaf students and listener students, mainly because of their linguistic inability to communicate and interact with one another. It was noticeable that the activity of copying was used more frequently than any other activity as a way of learning the English Language. Data suggest that many problems and challenges faced in the teaching of the target language for deaf students has its roots in the Brazilian educational system, which does not yet offer an ideal and high quality education for both teachers and student.